2020
DOI: 10.1155/2020/6102824
|View full text |Cite
|
Sign up to set email alerts
|

An Image Encryption Algorithm Based on Hyperchaotic System and Variable-Step Josephus Problem

Abstract: In this paper, an image encryption algorithm based on a hyperchaotic system and variable-step Josephus problem is proposed. Based on an in-depth analysis of the classic Josephus problem, a new variable-step Josephus problem that combines the pseudorandom sequence with the Josephus problem is proposed. Firstly, the hash value of the plaintext image is calculated, which is converted to the initial value of the chaotic system. Secondly, the chaotic system is iterated to generate four pseudorandom sequences X, Y, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Additionally, statistical analysis is of vital importance to determine strength of encrypted data. The effectiveness of the hyperchaotic system used in this work has been reported in [ 67 , 68 ] by successfully subjecting it to various tests of Statistical Test suite (NIST SP 800-22).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, statistical analysis is of vital importance to determine strength of encrypted data. The effectiveness of the hyperchaotic system used in this work has been reported in [ 67 , 68 ] by successfully subjecting it to various tests of Statistical Test suite (NIST SP 800-22).…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that this paper can encrypt the color image very fast. According to the comparison in Table 13, this work may run faster than some other encryption algorithms [2], [25], [40], [41]. To sum up, the time complexity of the proposed encryption scheme is high, and it can be well applied to image secure communication.…”
Section: J Speed Analysis and Complexitymentioning
confidence: 99%
“…Note that the differences in execution time depends on multiple factors, including the algorithm itself, the machine specifications on which the algorithm is run (i.e., processing power and available memory), as well as the software running the algorithm. Note that in [77,[80][81][82], the software of choice is Mathworks Matlab ® , whereas the proposed scheme is programmed on Wolfram Mathematica ® . The average encryption time of the proposed image encryption scheme is 0.61 Mbps.…”
Section: Execution Time Analysismentioning
confidence: 99%